People Analytics as a Job Demand or Resource - Biba, Sindi; Laumer, Sven (European Conference on Information Systems, 2024)
Considering the potential that People Analytics has on influencing business outcomes, but at the same time the requirement that it poses for HR professionals to have a variety of skills in order to successfully make use of PA, we introduce a theoretical model, that in addition to the job demands and resources of the JD-R model, presents a third component, the PA as both a job resource and a job demand. Preliminary results of the survey reveal that HR professionals perceive People Analytics as a resourc
Keywords: People Analytics; JD-R model; PA job demands; PA job resources.